Colonização do Brasil pela garça-vaqueira (Bubulcus ibis): distribuição intercontinental da variação genética determinada por dados genômicos - Silva, Fagner Miguel da (2019)
The cattle egret, Bubulcus ibis (Linnaeus, 1758), is a species of bird with high colonization capacity and invading potential. During the last century, this species has considerably expanded its geographical distribution and the size of its populations. Currently, Bubulcus ibis occurs in much of the African continent, southern Europe and the Americas. The main objective of this work was, based on the distribution of genetic variation, to infer the current pattern of genetic structure and a possible invasion route that explained the process of colonization of Brazil by Bubulcus ibis. To reach it, a draft genome of the species was assembled and new genetic markers, 2,751 SNPs and 22 microsatellites, were prospected. To assess the distribution of genetic variation and connectivity among populations, we estimated: a) indices of genetic diversity and measures of population genetic differentiation, b) migration rates per generation, patterns of population division and historical mix and effective migration surfaces. In addition, it was evaluated whether a geographic and/or adaptive pattern explained the genetic variation distribution, searching for potential SNPs under selection and testing the adequacy of the data to an isolation by distance model. Using information from 2,751 SNPs and eight prospective microsatellite loci, it was determined that, although with similar levels of genetic diversity, there is genetic structuring between the populations of Bubulcus ibis from the native and colonized areas (a more representative genetic cluster for each area). The estimated proportions of genetic ancestry showed a connection between African populations (Guinea-Bissau and Senegal) and the Brazilian northeast (Fernando de Noronha and Pernambuco). This result is supported by the most likely migration route inferred by the patterns of division and historical population mix (from Guinea Bissau to Pernambuco). Also, effective migration modelling detected a resistance to gene flow between Brazilian populations and southern Africa. The absence of potentially selective SNPs and the positive correlation between genetic and geographic distances indicated that the geographic factor is more determinant than the adaptive factor for the genetic structuring found. The most likely route of invasion of Bubulcus ibis is the Northeast of Brazil and not the North of the country (where the first record was made in 1964), with indications that departures in the native area still occur or occurred in the center-west African.